Enhancing Light Absorption and Charge Transfer Efficiency in Carbon Dots through Graphitization and Core Nitrogen Doping. Issue 23 (2nd May 2017) - Martindale, Benjamin C. M.; Hutton, Georgina A. M.; Caputo, Christine A.; Prantl, Sebastian; Godin, Robert; Durrant, James R.; Reisner, Erwin
Abstract: Single‐source precursor syntheses have been devised for the preparation of structurally similar graphitic carbon dots (CDs), with (g‐N‐CD) and without (g‐CD) core nitrogen doping for artificial photosynthesis. An order of magnitude improvement has been realized in the rate of solar (AM1.5G) H2 evolution using g‐N‐CD (7950 μmolH2  (gCD ) −1  h −1 ) compared to undoped CDs. All graphitized CDs show significantly enhanced light absorption compared to amorphous CDs (a‐CD) yet undoped g‐CD display limited photosensitizer ability due to low extraction of photogenerated charges. Transient absorption spectroscopy showed that nitrogen doping in g‐N‐CD increases the efficiency of hole scavenging by the electron donor and thereby significantly extends the lifetime of the photogenerated electrons. Thus, nitrogen doping allows the high absorption coefficient of graphitic CDs to be translated into high charge extraction for efficient photocatalysis. Abstract : Carbon dots are investigated for solar H2 production and a number of critical structure–activity relationships are determined for the first time. Nitrogen‐doping of the core structure is established as a strategy to enhance charge‐transfer reactions in graphitic carbons dots, which also demonstrate strong light absorption.